Menangani Overthinking Dengan Mindfulness Therapy - Alivia Khoirunnisa; Marsya Andini; Sri Mulyeni (Populer: Jurnal Penelitian Mahasiswa, 2025)
This study examines the effectiveness of mindfulness therapy in overcoming overthinking in Al Falah Dago High School students. The therapy was given to 30 students of Al Falah Dago High School. Overthinking is an excessive mindset that often triggers anxiety, especially among Generation Z who are exposed to technology and social media. The mindfulness therapy used is the STOP technique (Stop, Take a breath, Observe, Proceed) to make students more focused on the present moment. With the One Group Pretest-Posttest research design, the results showed an increase in the average level of students' mindfulness after the application of mindfulness therapy using the STOP technique. Before the intervention, the mean score of students' mindfulness was 15, and after the intervention, the score increased to 16.5. This study provides insight into the importance of mindfulness as a strategy to manage anxiety and build better mental balance.